Activation of peroxymonosulfate by base: Implications for the degradation of organic pollutants. (May 2016) - Qi, Chengdu; Liu, Xitao; Ma, Jun; Lin, Chunye; Li, Xiaowan; Zhang, Huijuan
Abstract: Increasing attention has been paid to environmentally friendly activation methods of peroxymonosulfate (PMS) in advanced oxidation processes (AOPs) for organic pollutant elimination. This work demonstrates that Base can be applied as a novel activator for PMS. The Base/PMS system, at ambient temperature, was able to degrade a variety of organic pollutants, including acid orange 7 (AO7), phenol and bisphenol A. In subsequent experiments with AO7, the decolorization rates for AO7 followed pseudo-first-order kinetics, with rate constant values ranging from 0.0006 to 0.1749 min −1 depending on the operating parameters (initial PMS, Base, AO7 concentrations and reaction temperature). Furthermore, the mechanism for PMS activation by the Base was elucidated by radical scavenger ( tert –butyl alcohol, methanol, sodium azide and p −benzoquinone) and electron spin resonance trapping studies. The results revealed that superoxide anion radical and singlet oxygen other than sulfate radical were the primary reactive oxygen species in the Base/PMS system. The findings of this study present a new pathway for PMS activation and provide useful information for the treatment of wastewater. Graphical abstract: Highlights: Base can activate peroxymonosulfate at a weakly basic environment. Base/peroxymonosulfate system is able to degrade a variety of organic pollutants. Superoxide radical and singlet oxygen may be the dominating reactive oxygen species.